Miliary tuberculosis presenting with acute respiratory distress syndrome in a patient with Down syndrome - Novković, Ljiljana; Lazić, Zorica; Petrović, Marina; Vujić, Ana; Stojković, Andjelka; Čekerevac, Ivan (Vojnosanitetski pregled, 2021)
Introduction. Miliary tuberculosis (TB) is a rare and potentially fatal form of disseminated TB. It is caused by a widespread haematogenous dissemination of Mycobacterium tuberculosis from an active caseous focus to different organs. Sometimes it can have an acute presentation with a rapid-onset clinical deterioration and death. Miliary TB complicated with an acute respiratory distress syndrome (ARDS) requiring mechanical ventilation (MV) is rare, even in countries with a high incidence of TB. Case report. A 35-year-old woman with Down syndrome (DS) was admitted to the Clinic for Pulmonology, Clinical Centre Kragujevac, due to an evaluation of cough and weight loss during last 2 months. Laboratory findings revealed anaemia, leukocytosis, elevated C-reactive protein (CRP) and hypoalbuminemia. A chest x-ray showed bilateral reticulonodular shadows, predominantly in the mid and lower right lung lobes. A purified protein derivative (PPD) skin test and induced sputum smear for acid-fast bacilli (AFB) were both negative. On the fifth day following admission, her health condition suddenly declined, and after developing a moderate ARDS, she was put on the mechanical ventilation. Due to a high clinical suspicion of miliary TB and the fact that her life was compromised, an empirical anti-tuberculosis therapy was initiated. Despite all therapeutic and supportive measures, the patient expired 3 days later. The diagnosis of miliary TB was established post-mortem. Conclusion. Miliary TB should be kept in mind in patients with DS due to immunosuppression associated with deficient cell-mediated immunity. The development of ARDS as a complication of miliary TB is difficult to identify due to a low causal association. High clinical suspicion and a chest radiograph with a typical appearance of miliary pattern justify the initiation of empirical anti-tuberculosis treatment in such patients, as an attempt to change poor prognosis.